Nickel-Iron Alloy Nanoparticle-Decorated K2NiF4-Type Oxide as an Efficient and Sulfur-Tolerant Anode for Solid Oxide Fuel Cells - Wu, N.; Wang, W.; Zhong, Y.; Yang, G.; Qu, J.; Shao, Zongping (Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim, 2017)
We report a new nickel-iron alloy nanoparticle-decorated LaSrFe0.75Ni0.25O4 K2NiF4-type oxide with Ruddlesden-Popper structure (RP-LSFN), which performed as a high-performance sulfur-resistant anode prepared by using an infiltration method for solid oxide fuel cells (SOFCs) with LaSrFeNiO6-d double perovskite (DP-LSFN) as the precursor. A reduction converts the DP-LSFN phase into mixed phases containing the RP-LSFN and FeNi3 nanoparticles. The morphology, thermal expansion behavior, sulfur tolerance, and electrochemical activity for hydrogen oxidation of this FeNi3 nanoparticle-decorated, RP-LSFN-infiltrated anode are investigated. An electrolyte-supported SOFC with this infiltrated anode generates a high power output of 541mWcm-2 at 800°C operated with 1000ppm H2S-H2 as the fuel, which compares favorably to that with pure H2 fuel. A single cell with this anode demonstrates favorable stability at 800°C during 90, 40, and 20h operation with H2 containing 100, 200, and 1000ppm H2S, respectively.